Pakistan: Failed State, Weak or Collapsed - Priego, Alberto (UNISCI Discussion Papers, 2012)
Since its independence in 1947 Pakistan has suffered from some structural difficulties, which have bundered its development as state. Thus among other problems we can stress the existence of very heterogeneous ethnic groups in the Northern and Eastern provinces or the problem of drug trafficking in most of the country. These circumstances have led to the inclusion of Pakistan in the failed/failing states indexes. The aim of the article is to clarify to what extent Pakistan can be considered a weak, failed, failing or even a collapsed state.